Kinerja Badan Permusyawaratan Desa Dalam Mewujudkan Pemerintahan Yang Demokratis (Studi di Desa Ciledug, Kabupaten Bekasi) - Elinda Suci Damayanti; Evi Priyanti (Universitas Muhammadiyah Sumatera Utara, 2023)
In order to realize democratic, open and accountable government, regional autonomy provides space for the community to contribute to development activities. This allows society to become both the object and subject of development. By using indicators of productivity, service quality, responsiveness, responsibility and accountability. This research aims to evaluate and improve the performance of BPD in realizing democratic governance. Using qualitative descriptive research methods with data sources from observation, interviews and documentation. Based on the results of the study, the effectiveness of BPD Ciledug's performance in terms of productivity is good looking at the quality, and quantity is adequate, the quality of services provided is quite good, it's just that the lack of communication intensity between BPD and the community, the responsiveness provided by BPD Ciledug to the community is quite good but there are obstacles, namely the lack of understanding of the community in receiving information due to the low level of education it has. In carrying outits duties and obligations, the responsibility of BPD institutions is in accordance with applicable regulations. According to the community, in terms of accountability, the village government together with BPD have been transparent and open in organizing village government.